Nearpod: A Web Based Tool to Promote Students’ Engagement in ESP Class - Metaria, Metaria; Basthomi, Yazid; Zen, Evynurul Laily (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
The call for new ways to engage students in this digital era is especially urgent. This research documents how a web-based tool called Nearpod can promote student engagement in ESP class by exploring behavioral and affective domains. By using a self-report questionnaire and observing the Nearpod post-session report, the data gained will be interpreted using descriptive statistical analysis. Results show that the level of behavioral engagement is 4.59 with attention and concentration as the highest contributing factor. The affective engagement obtains 4.42 value with vitality as the indicator with the highest score. Additionally, the observation results are also aligned with the findings from the self-report questionnaire. Some benefits and drawbacks of implementing Nearpod in ESP classroom are also explored.